Ring-Expansion Metathesis Polymerization Initiator Design for the Synthesis of Cyclic Polymers - Morrison, Christine M.; Golder, Matthew R. (Synlett, 2022)
Cyclic polymers are of increasing interest to the synthetic and physical polymer communities due to their unique structures that lack chain ends. This topological distinction results in decreased chain entanglement, lower intrinsic viscosity, and smaller hydrodynamic radii. Many methods for the production of cyclic polymers exist, however, large-scale production of architecturally pure cyclic polymers is challenging. Ring-expansion metathesis polymerization (REMP) is an increasingly promising method to produce cyclic polymers because of the mild and scalable reaction conditions. Herein, a brief history of REMP for the synthesis of cyclic polymers with both ruthenium and non-ruthenium initiators is discussed. Even though REMP is a promising method for synthesizing cyclic polymers, state-of-the-art methods still struggle with poor molar mass control, slow polymerization rates, low conversion, and poor initiator stability. To combat these challenges, our group has developed a tethered ruthenium-benzylidene initiator, CB6, which utilizes design features from ubiquitous Grubbs-type initiators used in linear polymerizations. These structural modifications are shown to improve initiator kinetics, enhance initiator stability, and increase control over the molar mass of the resulting cyclic polymers.1 Introduction2 Ring-Expansion Metathesis Polymerization (REMP) with Ruthenium Initiators3 New Developments in Ruthenium Ring-Expansion Metathesis (REMP) Initiator Design4 Ring-Expansion Metathesis Polymerization (REMP) with Non-Ruthenium Initiators5 Conclusions
Keywords: ring expansion; macrocycles; metathesis; ruthenium; polymers; carbene complexes